Fratelli inermi, fratelli in armi. La Prima Guerra Mondiale come etica in uno scenario senza etica? - Sandonà, Leopoldo (Filosofia Morale/Moral Philosophy, 2023)
The brother kills the brother on the (battle)field. The cry of injustice raises to God, who breaks the circle of revenge dictating not to touch the killer. The famous biblical passage can adequately introduce the reflection on the ethics of war, starting from the World War I scenario, a conflict that for its novelty for the contemporary age represents an analogatum princeps for a reflection on war.